Novel Cold-Inducible RNA-Binding Protein (CIRBP) in goat spermatozoa: A possible cryo-stress reliever during the process of Cryopreservation - ARANGASAMY, A; BACKIALAKSHMI, S; SHARANYA, J N; KRISHNAIAH, M VENKATA; SELVARAJU, S; ROY, K S; REDDY, I J; BHATTA, R (The Indian Journal of Animal Sciences, 2022)
The great expectation of the dairy owners from the frozen semen industry is quality semen with high fertility. Many researchers concentrate in this area to produce frozen semen of high quality and fertility. However, the problem still exists to minimize or reduce the cryoinjury related damages that occur during the process of cryopreservation with the use of all kinds of semen additives. The success rate of the additives added semen is variable at a larger scale. Therefore, any new molecules which can effectively prevent or minimize the cryoinjury are warranted and it could be low cost substances. Our incidental finding and protein identification with molecular weight ≈ 19 kDa (cold-inducible RNA-binding protein CIRBP) in goat spermatozoa seems to be effective in minimizing cryoinjury. The identified CIRBP was confirmed via Western blotting. In future, further studies are needed to confirm the molecular mechanism of the CIRBP on the cryoinjury as semen additives, and application of this protein added semen in the field to improve the level of conception rate in cattle.